STRESS-BASED FATIGUE LIFE MODEL UNDER ASYMMETRICAL LOADS - SU YunLai; LU Shan; DONG DengKe; CHEN XianMin; CHEN Li (Jixie qiangdu)
The key components in aircraft will be subjected to typical asymmetric loads in service,thus their fatigue behavior can be inevitably strongly affected by the mean stress effect. The modified Walker model employs the multiple-nonlinearfitting method to deal with fatigue test data under various stress ratios,by which the influence of material and maximum stress on mean stress effect can both be considered. Eighteen sets of fatigue test data from twelve kinds of aeronautical materials in various loading conditions were employed to validate the predict accuracy of modified Walker model,and the results were compared with other commonly used models. The study shows that the influence of maximum stress on mean stress effect varies with materials,while the prediction accuracy of the modified Walker model for each group of test data is better than that any other candidate models to varying degrees.